Rozwój mowy i komunikacji dziecka z uszkodzonym słuchem - Olempska-Wysocka, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article treats on complexity of speech development, communication process of child with damaged hearing. Article emphasizes factors defining different language and communication competences. Hearing impairment leads to self-expression being delayed. Mentioned delays, could be quantitative (active and passive vocabulary, subordinate to the chronological age of the child) and qualitative (numerous, different disorders of articulation, semantic errors, problems with understanding simple commands).